The reversible discrete failure of education. A critique on the concept of education from the educational inspection - Manuel Torres Vizcaya (ADIDE Federación, 2014)
The work thinks, beyond the eruptions and current situations of the educational system, about the significance of conceiving a clear concept of education. Starting, with satisfied and passive character of the inspector of education before the great importance of the education, it is proposed a critical consideration about the system, aiming at the decisive contributions that might be made to this process from the inspection.